2002
DOI: 10.5194/angeo-20-957-2002
|View full text |Cite
|
Sign up to set email alerts
|

The relativistic electron response in the outer radiation belt during magnetic storms

Abstract: Abstract. The relativistic electron response in the outer radiation belt during magnetic storms has been studied in relation to solar wind and geomagnetic parameters during the first six months of 1995, a period in which there were a number of recurrent fast solar wind streams. The relativistic electron population was measured by instruments on board the two microsatellites, STRV-1a and STRV-1b, which traversed the radiation belt four times per day from L ∼1 out to L ∼7 on highly elliptical, near-equatorial or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 29 publications
2
78
0
4
Order By: Relevance
“…Furthermore trends observed in the data were similar to trends observed in the solar wind velocity distributions (see Table 2) linking the solar wind and the outer electron belt in agreement with earlier studies which used different techniques (e.g. Blake et al, 1997, Iles et al, 2002 and references therein).…”
Section: Outer Electron Radiation Beltsupporting
confidence: 78%
“…Furthermore trends observed in the data were similar to trends observed in the solar wind velocity distributions (see Table 2) linking the solar wind and the outer electron belt in agreement with earlier studies which used different techniques (e.g. Blake et al, 1997, Iles et al, 2002 and references therein).…”
Section: Outer Electron Radiation Beltsupporting
confidence: 78%
“…Iles et al, 2002), suggesting that substorm activity may be important. Meredith et al (2001) performed a detailed statistical analysis of the plasma wave data from the CRRES spacecraft, and showed that outside of the plasmapause the chorus activity was largely substorm-dependent and all chorus emissions were enhanced when the substorm activity was enhanced.…”
Section: Resultsmentioning
confidence: 99%
“…This variability is caused by an imbalance between acceleration, transport, and loss processes all of which become enhanced during geomagnetic storms (Horne, 2002;Thorne et al, 2005;Horne et al, 2006;Summers et al, 2007). The ratio of post-storm to pre-storm flux was found related to the solar wind speed (Paulikas and Blake, 1979;Reeves et al, 2003) and the direction of the IMF Bz during the storm recovery phase (Iles et al, 2002). On the other hand, Ukhorskiy and Sitnov (2008) suggested that the outer belt can respond differently to similar solar wind driving.…”
Section: Introductionmentioning
confidence: 99%